A Multiethnic Asian Perspective of Presumed Consent for Organ Donation: A Population-Based Perception Study - Muthiah, Mark D.; Chua, Melissa Sin Hui; Griva, Konstadina; Low, Ivan; Lim, Wen Hui; Ng, Cheng Han; Hwang, Jeff Y. F.; Yap, Jason C. H.; Iyer, Shridhar G.; Bonney, Glenn K.; Anantharaman, Vathsala; Huang, Daniel Q.; et al. (Frontiers in Public Health, 2021)
Background Organ shortage is still a world-wide problem, resulting in long waiting lists for kidney, liver and heart transplant candidates across many transplant centres globally. This has resulted in the move towards presumed consent to increase deceased organ donation rates. However, there remains a paucity of literature on public attitude and barriers regarding the opt-out system, with existing studies limited to Western nations. Therefore, this study aimed to understand public sentiment and different barriers towards organ donation from the perspective of Singapore, a highly diverse and multiethnic Asian society. Methods A cross-sectional community semi-structured interview was conducted in a public housing estate in Singapore. Pilot test was undertaken before participants were interviewed face-to-face by trained personnel. All statistical evaluations were conducted using Stata. The χ2 test compared subgroups based on patient characteristics while multivariable logistic regression identified predictors of willingness to donate/ assent. Effect estimates were quantified using odds ratio (OR). Findings Out of 799 individuals, 85% were agreeable to organ donation after death and 81% were willing to assent to donations of family members’ organs, which declined by 16% (p < 0.001) after a clinical scenario was presented. Demographic factors including ethnicity, education, marital and employment status affected willingness to donate and assent. Knowledge correlated significantly with willingness to donate and assent. In particular, knowledge regarding brain death irreversibility had the strongest correlation (AOR 2.15; 95% CI 1.60-2.89). Conclusions Organ donation rates remain low albeit presumed consent legislation, due to patient-level barriers, including but not limited to knowledge gaps, cultural values, religious backgrounds, and emotional impact at relatives’ death. To effectively boost donor rates, it is crucial for policy makers to invest in public education and improve transplant provisions and family protocols.